REVIEW OF RECOMMENDATIONS FOR THE MANAGEMENT OF THE ACUTE CORONARY SYNDROMES IN PATIENTS PRESENTING WITHOUT PERSISTENT ST-SEGMENT ELEVATION (ESC 2015). Part II - N. T. Vatutin; A. S. Smyrnova; D. V. Bort; L. A. Prokopenko; E. S. Uzun (Архивъ внутренней медицины)
Окончание. Начало читайте в Томе 6, номере 2(28)-2016 г.